A consistent creep model for high strength steels and numerical investigation of creep on restrained steel beams. (December 2021) - Al-azzani, Hisham; Wang, Weiyong; Li, Xiang
Abstract: Even though creep behavior in steel at elevated temperatures has been widely observed, the effect of creep on steel members is not fully understood yet due to the extensive range of steel grades. In this paper, a tension creep test on high-strength Q960 steel at high temperatures was performed. Based on the test data in this paper and available creep data on Q345, Q460, and Q690 steels, a consistent creep model for each steel according to the Fields & Fields creep model was proposed and validated by the comparison with the test data. In order to quantitatively investigate the effect of creep on fire response of restrained steel beams, a finite element model (FEM) was established to analyze the critical temperature of restrained steel beams in fire conditions, with and without considering creep strain generated in steel beams. This was also carried out to better understand the impact of high-temperature on steel beams with various steel grades under the influence of the same load. The verification of the FEM was achieved by comparing the results with experimental data on a restrained Q235 steel beam and Q690 cantilever steel beam. The study reveals that creep has a noticeable effect on the fire resistance of the restrained steel beams and that the effect varies from one type of steel to another. A comparison has been made to observe the effect of high-temperature creep on the critical temperature for each steel type. Graphical abstract: In this paper, a tension creep test on high-strength Q960 steel at high temperatures was performed. Based on the test data in this paper and available creep data on Q345, Q460, and Q690 steels, a consistent creep model for each steel according to the Fields & Fields creep model was proposed and validated by the comparison with the test data. In order to quantitatively investigate the effect of creep on fire response of restrained steel beams, a finite element model (FEM) was established to analyze the critical temperature of restrained steel beams in fire conditions, with and without considering creep strain generated in steel beams. This was also carried out to better understand the impact of high-temperature on steel beams with various types of steel under the influence of the same load. The verification of the FEM was achieved by comparing the results with experimental data on restrained Q235 steel beams. The study reveals that creep has a noticeable effect on the fire resistance of the restrained steel beams and that the effect varies from one type of steel to another. A comparison has been made to observe the effect of high-temperature creep on the critical temperature for each steel type. Unlabelled Image Highlights: High-temperature tensile creep tests on Q960 were carried out. A consistent creep model for high strength steels was proposed. A finite element model to predict fire respone of restrained steel beams was developed and calibrated by available test data. Effect of creep strain and steel type on fire-resistance of restrained steel beams was investigated.